THE ECONOMIC IMPORTANCE OF THE SPONTANEOUS FLORA WITHIN OLTENIA PLAIN, ROMANIA - Daniel RĂDUȚOIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The present paper deals with the results of the research conducted over a long period of time (i.e. about 25 years), on the economic importance of the spontaneous flora in the Oltenia Plain. The study was mainly motivated by the gradual decrease in the number of people who resort to traditional practices and by the widespread use of synthetic products, which have rapid but unhealthy effects. The analysis of the employment of useful species in this part of Oltenia highlights a worrying aspect: the use of spontaneous plants is age-dependant and it declines at younger ages. The medicinal species are still of great importance and they are used in almost all settlements within Oltenia Plain, although their use is more significant in rural areas and less important in urban ones. Unlike the pre-2000 period, when tinctorial species were employed to a greater extent, they are now used only occasionally, by the elderly.